1999
DOI: 10.1046/j.1420-9101.1999.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Below-threshold mortality: implications for studies in evolution, ecology and demography

Abstract: Evolutionary biologists, ecologists and experimental gerontologists have increasingly used estimates of age‐specific mortality as a critical component in studies of a range of important biological processes. However, the analysis of age‐specific mortality rates is plagued by specific statistical challenges caused by sampling error. Here we discuss the nature of this ‘demographic sampling error’, and the way in which it can bias our estimates of (1) rates of ageing, (2) age at onset of senescence, (3) costs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 65 publications
1
82
0
Order By: Relevance
“…Further addition of various treatments, although extending average lifespan, had no significant effect on G. Few changes in the initial mortality rate (A) were detected. The lack of a significant finding is not surprising, as it has been shown that A is highly variable (Promislow et al 1999). CHIL increased A for both daf-2 and clk1/daf-2 worms on DR, and dietary restricted daf-2 worms had a decreased A compared to dietary restricted N2 worms.…”
Section: Gompertz Analysismentioning
confidence: 88%
“…Further addition of various treatments, although extending average lifespan, had no significant effect on G. Few changes in the initial mortality rate (A) were detected. The lack of a significant finding is not surprising, as it has been shown that A is highly variable (Promislow et al 1999). CHIL increased A for both daf-2 and clk1/daf-2 worms on DR, and dietary restricted daf-2 worms had a decreased A compared to dietary restricted N2 worms.…”
Section: Gompertz Analysismentioning
confidence: 88%
“…Our sample sizes more than fulfil the minimum requirements for fitting mortality models [47]. Of the various mortality models fitted to our data, the Gompertz model fitted best (electronic supplementary material, table S4).…”
Section: (C) Statistical Analysesmentioning
confidence: 96%
“…In poikilotherms the effects of CR and temperature on longevity can be distinguished by the slopes of the mortality curves [19][20][21][22][23]. In Drosophila, chronic CR results in a delay in the onset of a detectable aging-related increase in mortality.…”
Section: Thermodynamic Effects and Specific Pathwaysmentioning
confidence: 99%